Penerapan Teknik Sinematografi Dalam Pembuatan Video Promosi Program Studi Ilmu Komunikasi Universitas Dharma Andalas - Azrel Aurellio; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The process of creating a short video as a promotional medium requires creativity and a deep understanding of the target audience. Every element in the video, from narration, visuals, music, to message delivery, must be well designed in order to create a deep impression and arouse the interest of prospective students. This project aims to explore and apply a semiotic approach to the creation of a short video, focusing on analyzing the signs and meanings contained in audiovisual content. Semiotics is the basis for understanding how symbols, colors, camera movements, and other visual elements can shape perceptions and improve communication effectiveness in promotional videos. By understanding the semiotic aspects, this video production is expected to be able to convey a deeper and more meaningful message, thus not only attracting attention but also building a strong image for the study program. Cinematography is the art and science of capturing and combining moving images to convey ideas, stories or visual experiences to an audience. The term comes from the Greek kinema, meaning movement, and graphein, meaning to write or record. Thus, cinematography literally means “writing with movement.” The cinematography techniques applied in this video production, such as angle selection, lighting, and camera movement, play an important role in creating interesting and informative visuals. As a cameraman, the main role in this process is to ensure that every visual element displayed can support the delivery of the message optimally. With the proper application of cinematography techniques, such as the selection of appropriate angles, aesthetically pleasing image composition, and mood-supporting lighting, this video successfully presents professional and attractive visuals. In addition, the use of various shooting techniques, such as tracking shots to capture the dynamics of student activities as well as high angles and close-ups to highlight supporting facilities, contributed to enriching the visual appearance. After going through all stages of production, the resulting promotional video is able to represent the identity, values, and advantages of the Dharma Andalas University Communication Studies Program well. This video is not only a promotional tool, but also an effective communication medium in building institutional branding and increasing attractiveness for prospective students. With a combination of a strong visual strategy and the right communication approach, it is hoped that this video can have a positive impact in strengthening the academic image and attracting more students to join this study program.